(untitled) (Світ фінансів, 2017)
Новосад Л. Я. Фіскальне адміністрування в Україні: проблеми теорії та практики. Розглянуто сутність і призначення фіскального адміністрування. Проналізовано проблеми функціонування складових фіскального адміністрування в Україні. Novosad L. Fiscal Administration in Ukraine: Problems of Theory and Practice. In the article essential theoretical points of fiscal administration are investigated. Problems of functioning of parts fiscal administration in Ukraine are analysed.